2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34827
|View full text |Cite
|
Sign up to set email alerts
|

Information-seeking Behavior Among First-year Engineering Students and the Impacts of Pedagogical Intervention

Abstract: teaches Communications in the Engineering Profession at the University of Waterloo. George specializes in developing engineering-communications curricula with authentic, discipline-specific materials in partnership with engineering firms and clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…The literature recognizes the need for critical thinking and reasoning but there is not weight given to how students are finding and generating ideas-which largely are coming through informal information seeking (peers, blogs, Reddit, colleagues, mentors, social media, etc.) [14]. We know students are doing this, but we do not consider how we train students in this as well as training them to find traditionally academic sources (journals, textbooks, standards, etc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature recognizes the need for critical thinking and reasoning but there is not weight given to how students are finding and generating ideas-which largely are coming through informal information seeking (peers, blogs, Reddit, colleagues, mentors, social media, etc.) [14]. We know students are doing this, but we do not consider how we train students in this as well as training them to find traditionally academic sources (journals, textbooks, standards, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Within the PBL model, we provide students with a problem and expect an outcome. Students entering into undergraduate engineering programs need specific training and are in the process of building the skills and knowledge they need to become practicing engineers, but the fact that they do not, and in fact should not yet have these skills around information, is something that is not specifically outlined in existing pedagogy, or often explicitly in practice [14]. By implicitly guiding students towards information as a means to an end, we miss an opportunity to engage them at a critical point in their education, making this practice a habit and ultimately making the transition to professional life easier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atman and colleagues (1999) suggested one explanation for the differences in these behaviors is that first-year engineering students may not be aware of the need to gather information before developing a solution. More recent research has found that first-year students' information literacy behavior also depends upon their personal investment or motivation in the project (Lamont et al, 2020). The researchers noted that when students thought the project was meaningful, students engaged in more information literacy behaviors.…”
Section: Introductionmentioning
confidence: 99%